Novel physiological analysis using blood flow velocity for colonic polyps: Pilot study - Kamba, Eiji; Murakami, Takashi; Tsugawa, Naoki; Nomura, Kei; Haga, Keiichi; Akazawa, Yoichi; Fukushima, Hirofumi; Ueyama, Hiroya; Matsumoto, Kenshi; Shibuya, Tomoyoshi; Terai, Takeshi; Yao, Takashi; Nagahara, Akihito (Endoscopy International Open, 2024)
Real-time visualization of red blood cell flow inside subepithelial microvessels is performed with magnifying endoscopy. However, microvascular blood flow velocity in the colorectum has not been investigated. Here, we aimed to evaluate the blood flow velocity of microvessels of colonic polyps and to compare it with that of surrounding mucosa. We examined 50 lesions, including 30 adenomas (ADs) and 20 hyperplastic polyps (HPs). Blood flow velocities of lesions and their surrounding mucosa were evaluated using magnifying blue laser imaging (BLI) prior to endoscopic resection. Calculation of mean blood flow velocities was based on mean movement distance of one tagged red blood cell using split video images of magnifying BLI. Mean microvascular blood flow velocity was significantly lower in ADs (1.65±0.66 mm/sec; range 0.46–2.90) than in HPs (2.83±1.10 mm/sec; 1.07–4.50) or the surrounding mucosa (3.73±1.11 mm/sec; 1.80–6.20; P <0.001). The blood flow velocity rate compared with the surrounding mucosa was significantly lower in ADs (0.41±0.16; 0.10–0.82) than in HPs (0.89±0.25; 0.46–1.51; P <0.001). We found that mean microvascular blood flow velocity was significantly lower in ADs than in HPs and the surrounding non-neoplastic mucosa. These findings indicate that a novel dynamic approach with microvascular blood flow velocity using magnifying endoscopy may be useful in assessing physiological differences between ADs and HPs.
Keywords: Endoscopy Lower GI Tract; Polyps/adenomas/...; Diagnosis and imaging (inc chromoendoscopy, NBI, iSCAN, FICE, CLE...); Tissue diagnosis